2015
DOI: 10.3389/fmicb.2015.01313
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Ciliate Protozoa in the Rumen

Abstract: First described in 1843, Rumen protozoa with their striking appearance were assumed to be important for the welfare of their host. However, despite contributing up to 50% of the bio-mass in the rumen, the role of protozoa in rumen microbial ecosystem remains unclear. Phylogenetic analysis of 18S rDNA libraries generated from the rumen of cattle, sheep, and goats has revealed an unexpected diversity of ciliated protozoa although variation in gene copy number between species makes it difficult to obtain absolute… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

35
399
4
7

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 437 publications
(491 citation statements)
references
References 159 publications
35
399
4
7
Order By: Relevance
“…Moreover, Isotrichidae as well as cellulolytic ciliates disappeared from the rumen of sheep fed an "oil" ration after 10 and 21 days, respectively. Newbold et al (2015) suggested that ruminal ciliates digest as well as convert dietary fat, but a high lipid concentration in the ration is toxic to protozoa. Szumacher-Strabel (2010) reported that the genus Epidinium spp.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Moreover, Isotrichidae as well as cellulolytic ciliates disappeared from the rumen of sheep fed an "oil" ration after 10 and 21 days, respectively. Newbold et al (2015) suggested that ruminal ciliates digest as well as convert dietary fat, but a high lipid concentration in the ration is toxic to protozoa. Szumacher-Strabel (2010) reported that the genus Epidinium spp.…”
Section: Discussionmentioning
confidence: 99%
“…(E. ecaudatum and E. caudatum) participated in 30% of lipolysis process, but these ciliates were not identified in our study. According to Newbold et al (2015) the antiprotozoal effect of fat depends on the fatty acid composition. Medium chain fatty acids are more effective in controlling ciliate amount than polyunsaturated fatty acids.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, some protozoa groups have fibrolytic activity and play a key role in the early colonization of the fibre (Newbold, Fuente, Belanche, Morales, & McEwan, 2015). Their defaunation also decreases the fibrolytic microorganism concentration in the rumen (Newbold et al, 2015).…”
Section: Discussmentioning
confidence: 99%
“…Selain itu, protozoa sebagai predator diperlukan sebagai pengendali komunitas mikroorganisme di dalam rumen. Eliminasi protozoa ciliata meningkatkan suplai protein (dari mencerna protein bakteri) hingga 30%, dan mengurangi produksi metana hingga 11% [25].…”
Section: Biomassa Bakteri Dan Protozoaunclassified